A Comparative Study to Evaluate the Efficacy of Skin Microneedling and Platelet Rich Plasma (PRP) Combination Versus Skin Micro Needling Alone for the Treatment of Atrophic Facial Acne Scars Using Goodman and Baron’s Grading - Wazir, Humaira; Masaud, Faryal; Naeem, Hamid; Zahoor, Sikandar; Imran, Junaid; Akhtar, Ibrahim (Indus Journal of Bioscience Research, 2024)
BACKGROUND One unfortunate and permanent effect of acne vulgaris is atrophic scarring. The ailment is rather common and greatly affects the quality of life of the person. Tests of micro needling have been conducted both as a stand-alone therapy and in combination with chemical peeling, platelet-rich plasma, radiofrequency, subcision, and lasers. OBJECTIVE To assess the effectiveness of a combined treatment using skin micro needling and platelet rich plasma (PRP) compared to skin micro needling alone in treating atrophic facial acne scars. METHODOLOGY Randomized control trial (RCT) and comparative study were conducted in department of Dermatology, MTI/Lady Reading Hospital, Peshawar, for the duration of one year. Out of 100 patients 50 were included in each group in the study. Group-A was treated with skin micro needling and PRP while Group-B with skin micro needling alone for the treatment of atrophic facial acne scars. RESULTS Mean age of the patients of group-A was 28.0±6.2 and group-B was 29.4±5.2 years. Females were predominant in both groups. Mean duration of symptoms in group-A was 9.0±8.5 month and in group-B 10.9±8.5 months. Combined therapy with micro needling and PRP reported 82% efficacy while skin micro needling alone showed 62% efficacy for the management of atrophic scars from face acne (p=0.026). CONCLUSION In conclusion, combination of skin micro needling and platelet rich plasma (PRP) is more effective than needling alone for the treatment of atrophic facial acne scars.